Self Openness of PLWHA: A Literature Analysis on the Role of Social Media in Building Social Support - Dwianita, Dwianita; Maharani, Blangi Intan; Sembiring, Putri Sosanti (Program Pascasarjana UIN Sumatera Utara, 2025)
Stigma and discrimination against people living with HIV/AIDS (PLWHA) remain a major obstacle to achieving an optimal quality of life, especially in terms of self-disclosure and access to social support. In the midst of the rapid development of digital technology, social media has emerged as a potential online space that can be utilized by PLWHA to express their identity and build social support networks. This study aims to analyze the role of social media in supporting the self-disclosure of PLWHA and its contribution in forming a supportive online community. The method used is a literature review with a descriptive analysis approach that examines various academic studies from the last 5 years published from 2019 to 2024 through databases such as PubMed, JMIR, Springer, PMC and Google Scholar. The results show that social media provides a safe space for PLWHA to manage their identity narratives, increase self-confidence, and obtain validation and emotional support from online communities. However, the dilemma between the need for openness and the risk of stigma and invasion of privacy remains a significant challenge. This study recommends that future research emphasize qualitative exploration of PLHIV's direct experiences, as well as the development of inclusive and safe digital platform policies and designs to support the sustainability of empowering self-disclosure.